Analysis of students' conception of the generation and disposal of solid waste in the school environment / Análise da concepção dos alunos sobre a geração e descarte de resíduos sólidos no ambiente escolar - Maurício Cordeiro Freire; Anne Mírian da Silva Gomes (); Eliane Lima da Silva Oliveira; Jaqueline Araújo de Oliveira; Maria Janiele Barbosa de Farias; Janaína Kívia Alves Lima (Universidade Estadual de Alagoas, 2016)
The management of solid waste has been singled out by environmentalists as one of the most serious environmental concerns of today, since too much consumerism has taken hold of society and affected urban sustainability. Reduce waste production depends on changes in patterns of production and consumption of society. This study aimed to analyze the design of students in high schools, on the generation and disposal of solid waste in the school environment, as well as sensitize them about the theme. The survey was conducted in three stages, the first was carried out a visit to the school applying semi-structured questionnaire containing questions regarding the generation and disposal of garbage produced to high school students. Later he was promoted a lecture about the management of solid waste in school and at the end was reapplied the same questionnaire to ascertain the level of assimilation of the subject after the lecture. Through qualitative and quantitative analysis of the questionnaires it was revealed that prior knowledge of the students regarding the generation of waste at school was poor and that the promotion of the lecture with the theme "the importance of solid waste for environmental education", was effective promoting a broad impact, and discussion questions about the theme. It is considered of paramount importance to address issues related to solid waste and its management in the educational environment, reinforcing the idea that the school community needs an awareness-training of such problems.